Pathway connectivity and signaling coordination in the yeast stress‐activated signaling network - Deborah Chasman; Yi‐Hsuan Ho; David B Berry; Corey M Nemec; Matthew E MacGilvray; James Hose; Anna E Merrill; M Violet Lee; Jessica L Will; Joshua J Coon; Aseem Z Ansari; Mark Craven; et al. (Molecular Systems Biology)
Abstract Stressed cells coordinate a multi‐faceted response spanning many levels of physiology. Yet knowledge of the complete stress‐activated regulatory network as well as design principles for signal integration remains incomplete. We developed an experimental and computational approach to integrate available protein interaction data with gene fitness contributions, mutant transcriptome profiles, and phospho‐proteome changes in cells responding to salt stress, to infer the salt‐responsive signaling network in yeast. The inferred subnetwork presented many novel predictions by implicating new regulators, uncovering unrecognized crosstalk between known pathways, and pointing to previously unknown ‘hubs’ of signal integration. We exploited these predictions to show that Cdc14 phosphatase is a central hub in the network and that modification of RNA polymerase II coordinates induction of stress‐defense genes with reduction of growth‐related transcripts. We find that the orthologous human network is enriched for cancer‐causing genes, underscoring the importance of the subnetwork's predictions in understanding stress biology.